1977
DOI: 10.1161/01.cir.55.2.361
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac function in total anomalous pulmonary venous return before and after surgery.

Abstract: Cardiac performance was evaluated in 12 infants with isolated total anomalous pulmonary venous return. Four had significant pulmonary venous obstruction and severe pulmonary hypertension (group A). Eight had no obvious venous obstruction, and the pulmonary pressures were lower (group B). In all subjects, right ventricular end-diastolic volume was increased (197% of predicted normal) and its ejection fraction was normal. Left ventricular volume was, generally speaking, still in the normal range (87% of predicte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
1
1

Year Published

1978
1978
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 21 publications
0
30
1
1
Order By: Relevance
“…Recent haemodynamic studies have shown normal cardiac function after surgical correction performed in infancy (Mathew et al, 1977), and add further support to this policy. A comparison of haemodynamic studies in patients who have undergone total correction at a later age, with those who have been corrected in infancy, is awaited with interest.…”
Section: Discussionmentioning
confidence: 71%
“…Recent haemodynamic studies have shown normal cardiac function after surgical correction performed in infancy (Mathew et al, 1977), and add further support to this policy. A comparison of haemodynamic studies in patients who have undergone total correction at a later age, with those who have been corrected in infancy, is awaited with interest.…”
Section: Discussionmentioning
confidence: 71%
“…with that collected by Mathew et al . [17] and Nakazawa et al . [20] suggests : (a) preoperatively, the left ventricular size, ejection fraction, and systolic output are often decreased ; (b) these decreases probably result from a decreased volume load to the left ventricle ; (c) pulmonary symptoms result from venous obstruction and not from ventricular dysfunction ; and (d) decreased left ventricular size and function do not affect operative mortality and are reversed with early repair.…”
Section: Discussionmentioning
confidence: 96%
“…[12][13][14] Two explanations have been proposed: the large left-to-right shunt under-fills the left-sided chambers; 15 and during embryologic development, the common pulmonary vein fails to fuse with the LA body. 16 Some surgical approaches using patch augmentation to increase LA capacity were designed to obviate this shortcoming.…”
Section: Discussionmentioning
confidence: 99%